In Darfur an account of the sultanate and its people - Tūnisī, Muḥammad Ibn-ʿUmar at- 1789-1857 (New York University Press, 2018)
In Volume One, al-Tunisi relates the history of his much-traveled family, his journey from Egypt to Darfur, and the reign of the noted sultan 'Abd al-Rahman al-Rashid. In Volume Two al-Tunisi describes the geography of the region, the customs of Darfur’s petty kings, court life and the clothing of its rulers, marriage customs, eunuchs, illnesses, food, hunting, animals, currencies, plants, magic, divination, and dances. In Darfur combines literature, history, ethnography, linguistics, and travel adventure, and most unusually for its time, includes fifty-two illustrations, all drawn by the author
Keywords: Geschichte 1851; Darfur; Sudan; Darfur (Sudan) / History / 18th century; Darfur (Sudan) / History / 19th century; Darfur (Sudan) / Description and travel; Travel; Sudan / Darfur; 1700-1899; History; Quelle; Reisebericht